Perpindahan Panas Dan Penurunan Tekanan Pada Saluran Segiempat Dengan Rusuk V 90 Derajat - Khairul Umurani; Arya R. Nasution; D Irwansyah (Fakultas Teknik UMSU, 2021)
The augmentation of the heat transfer surface using ribs is often used in heat exchanger equipment, aiming to increase heat transfer between the main surface and its fluid. This study uses a rectangular channel with testing on the specimen the number of ribs V 2 with three lengths of 200 mm, a width of 150 mm, and plate thickness of 1 mm. Rectangular air duct consisting of a rectangular duct with dimensions of 150 mm x 75 mm and a length of 2000 mm, suction fan, plate-type electric heater, airflow straightener, U monometer, anemometer, ampere meter, voltmeter, speed controller, and thermocouple. The parameters varied were the incoming airflow velocity, namely 1 m / s, 2m / s, 3 m / s, 4 m / s, and 5m / s. The experimental results heat transfer coefficient at tighter ribs provides better heat transfer. The pressure drop in Pa at the tight rib distance is higher than the pressure drop at the spaced rib spacing